Silyloxy Amino Alcohol Organocatalyst for Enantioselective 1, 3‐Dipolar Cycloaddition of Nitrones to α, β‐Unsaturated Aldehydes. Issue 33 (16th October 2015) - Otsuki, Teppei; Kumagai, Jun; Kohari, Yoshihito; Okuyama, Yuko; Kwon, Eunsang; Seki, Chigusa; Uwai, Koji; Mawatari, Yasuteru; Kobayashi, Nagao; Iwasa, Tatsuo; Tokiwa, Michio; Takeshita, Mitsuhiro; et al.
Abstract: The catalytic activity of a simple amino alcohol that contains a bulky super silyl group [i.e., tris(trimethylsilyl)silyl (TTMSS)] bonded to the oxygen atom at the γ‐position along with a primary amine moiety was examined in the enantioselective 1, 3‐dipolar cycloaddition of nitrones to α, β‐unsaturated aldehydes. The organocatalyst successfully provided optically active isoxazolidines in good chemical yields (up to 86 %) with excellent diastereoselectivities ( endo / exo, up to 96:4) and enantioselectivities (up to 97 %  ee ). Furthermore, the obtained isoxazolidines were easily converted into γ‐amino diols that contain three contiguous stereogenic centers. Abstract : An amino alcohol with a tris(trimethylsilyl)silyl (TTMSS) group was prepared, and its catalytic activity was examined in the enantioselective 1, 3‐dipolar cycloaddition of nitrones to α, β‐unsaturated aldehydes. Compound1 catalyzed the reaction to give isoxazolidines in good yields (up to 86 %) with excellent diastereoselectivities ( endo / exo, up to 96:4) and enantioselectivities (up to 97 %  ee ).